The determination on the effects of the sewing parameters to the seam strenght of the tencel fabrics [Tencel kumaşlarda dikiş parametrelerinin dikiş mukavemetine etkilerinin incelenmesi] - (:unkn) unknown (My University, 2010)
The most important quality problems in garments of the ready-made industry is the seam strength. Beside the garment quality and its performances, the seam strength, slippage of the seam, seam pucker etc. are also various factors that may effect. in this study, 4 different tencel fabrics with 6 different sewing yarns were used for the different weights and structures of fabrics were tested for their seam strengths and elongations with using different types of sewing yarns and seam densities. The results were analysed by using the SPSS software programme. it was observed that Tencel fabric's with basic structure have shown higher seam strength than the rib fabrics. As the sewing yarns get coarser the seam strength in weft, warp and and diagonal direction increases. As the sewing yarn gets finer the seam strength decreases and the highest strength was observed on the diagonal direction and the least strength was obtained on the warp direction of the fabric. Also as the seam density increases the strength and elongation were increased.
Keywords: Seam density; Seam direction; Sewing defect; Sewing strength; Tencel fabric